Sliding mode control in a mathematical model to chemoimmunotherapy: The occurrence of typical singularities - Rodrigues, Diego S.; Mancera, Paulo F.A. [UNESP]; Carvalho, Tiago; Gonçalves, Luiz Fernando [UNESP] (Elsevier, 2020)
The application of sliding mode control and piecewise smooth vector fields in cancer is an incipient research area. Here we propose a piecewise dynamics to explore chemoimmunotherapeutic strategies. We investigate the dynamic behavior of the discontinuous mathematical model and we observe the occurrence of typical singularities. The on-off treatment strategies are defined in terms of a time-dependent variable such as the number of cancer or immune cells.
Keywords: Cancer; Chemoimmunotherapy; Piecewise smooth vector fields; Typical singularities